Epidemiology of human papillomavirus-associated anogenital cancers in Granada: a three-decade population-based study - Dabán-López, Pablo; Fernández-Martínez, Nicolás Francisco; Petrova, Dafina; Rodríguez-Barranco, Miguel; Jiménez-Moleón, Jose Juan; Gutierrez, Javier; Sánchez, María-José (Frontiers in Public Health, 2023)
Introduction HPV infection is a common risk factor for all anogenital cancers. However, there are important differences in the epidemiology of anogenital cancers and these have not been compared considering diverse epidemiological indicators over a long period of time. To fill this gap, we investigated incidence, mortality, and survival trends of anogenital cancers over a period of three decades. Methods We conducted an observational registry-based study using data from the population-based cancer registry of Granada in southern Spain. We collected data on all incident cases of anogenital cancer (cervical, anal, penile, vulvar, and vaginal cancer) diagnosed between 1985 and 2017. We calculated crude and age-standardized incidence and mortality rates, and 1, 3, and 5-year overall and net survival. We further conducted time-trend analysis calculating annual percent changes (APC) for each cancer site. Results The incidence of anogenital cancers decreased slightly during the past 30 years, with the exception of vulvar cancer, where a slight increase was observed. Mortality decreased significantly for cervical cancer over the study period but increased non-significantly for the remaining cancer sites. Survival rates were similar to those reported in comparable countries and increased for cervical and vulvar cancer. Discussion Cervical cancer was the greatest contributor to the burden of anogenital cancers and showed a marked improvement in all indicators in comparison to the remaining cancer sites.